Being a caring leader - Lennick, Doug (FTPress Delivers, 2011)
This Element is an excerpt from Moral Intelligence: Enhancing Business Performance and Leadership Success (9780132349864) by Doug Lennick and Fred Kiel, Ph.D.. Available in print and digital formats. Compassion is the heart of leadership: lessons from the experiences of world-class executives. When you are a leader, embracing your responsibility to serve others flows into compassion. Actively caring about others means that you do things that actively support their personal choices. Sometimes, it means you care about others' goals as much as they do. At times, you might find yourself taking their goals more seriously than they feel able to...
Online resource; title from PDF title page (EBSCO, viewed January 23, 2018)
Keywords: Business ethics; Leadership -- Moral and ethical aspects; Success in business -- Moral and ethical aspects; Moral development; Morale des affaires; Leadership; Aspect moral; Succès dans les affaires; Aspect moral; Développement moral; BUSINESS & ECONOMICS; Business Ethics; Leadership; Moral and ethical aspects